Estimation of the Survival Function Using the New Mixed Distribution (Power Function-Truncated Burr III) With Application - Ghufran Khalid Abdulhussein, Dr. Raissan Abdalimam Zalan (Mathematical Statistician and Engineering Applications, 2022)
In this research, a new mixture of distributions (Power Function-Truncated Burr III) (MPF-TBIII) was proposed. The proposed model with finding some mathematical and statistical properties of the distribution. Then the parameters and survival function of the proposed distribution (MPF-TBIII) were estimated using different methods of estimation, which are the greatest possibility method (MLE) and the fractional estimation method (PS).Fractional estimators (PS) were the best in estimation at large sample sizes, and then the fractional estimators (PS) method was used. Estimating the survival function of corona patients.